The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/risa.13273
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Capital and the Risk of Maternal Labor and Delivery Complications: Hospital Scheduling, Timing, and Cohort Turnover Effects

Abstract: The establishment of interventions to maximize maternal health requires the identification of modifiable risk factors. Toward the identification of modifiable hospital-based factors, we analyze over 2 million births from 2005 to 2010 in Texas, employing a series of quasiexperimental tests involving hourly, daily, and monthly circumstances where medical service quality (or clinical capital) is known to vary exogenously. Motivated by a clinician's choice model, we investigate whether maternal delivery complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Staff shortages may also explain the lower levels of quality found in evening and night deliveries. Studies in the United States have shown that delivery complications tend to be higher during night shifts and on weekends and holidays, when hospitals are understaffed, and less experienced doctors are more likely to work . In low‐income countries, studies found that disrespectful and abusive experiences are more common, and women are more likely to be left alone during night shifts while there are fewer providers .…”
Section: Discussionmentioning
confidence: 99%
“…Staff shortages may also explain the lower levels of quality found in evening and night deliveries. Studies in the United States have shown that delivery complications tend to be higher during night shifts and on weekends and holidays, when hospitals are understaffed, and less experienced doctors are more likely to work . In low‐income countries, studies found that disrespectful and abusive experiences are more common, and women are more likely to be left alone during night shifts while there are fewer providers .…”
Section: Discussionmentioning
confidence: 99%
“…These are important findings. According to a recent study that included over 2 million births, delivery complications are higher during night shifts when hospitals are understaffed (18). Also, in developed countries, i.e.…”
Section: Discussionmentioning
confidence: 99%